Maggot Cultivation in Utilizing Organic Waste as a Form of MSME Development in Manduro Village: Budidaya Maggot Dalam Memanfaatkan Sampah Organik Sebagai Bentuk Pengembangan UMKM Desa Manduro - Kholifah, Nur; Pebrianggara, Alshaf; Hindarto, Hindarto; Lailia, Jauharotul; Vania, Talitha; Viyanti, Amalia; Quraini, Isyaffina; Bimo, Muhammad Nur (Procedia of Social Sciences and Humanities, 2022)
Garbage is one of the complex problems faced by a country.Based on its composition, waste is divided into several types, including organic waste.If the waste is not managed properly it will cause environmental damage and will disrupt community activities, especially Manduro Village.The purpose of this research is processing organic waste to reduce the amount of waste around the Manduro Village environment by using BSF fly larvae to cultivate Maggot so that it can be used as one of the UMKM that can be developed by Manduro Village.The people of Manduro Village regarding the procedures for budding da maggot.The results showed that the people of Manduro Village were very enthusiastic and could accept the material that was presented well and Budi Dava Maggot in the context of utilizing organic waste could be used as a form of UMKM in Manduro Village for the future.